The Effect Of Shuttle Run And Zig-Zag Drill Exercises On Soccer Dribbling Agilityon SSB Duta Fortuna U-13 - Vallent kunang putra challista; Moch Fahmi Abdulaziz (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This quasi-experiment-based quantitative research with a pretest-posttest design of two groups aims to analyze and compare the effect of shuttle run and zig-zag drill exercises on ball dribbling agility in SSB DUTA FORTUNA U-13 players. The research sample amounted to 20 players who were taken using saturated sampling techniques, then divided evenly into two groups to undergo a 3-week training program with a frequency of 3 times per week. Dribbling agility is measured using the dribbling agility test in seconds. The results of the Paired Samples T-Test analysis showed that both training methods had a significant influence on the improvement of dribbling agility (p < 0.001), where the shuttle run group experienced a decrease in average travel time by 0.634 seconds and the zig-zag drill group by 0.639 seconds. Based on the effect size analysis, both treatments were in the very large effect category, but the zig-zag drill showed slightly stronger values (Cohen's d = 21.582) than the shuttle run exercise (Cohen's d = 30.693). It can be concluded that both training methods effectively improve the dribbling agility of early age players, with the zig-zag drill making a slightly higher contribution due to its complex movement characteristics more resembling real situations in the game of soccer.